Maju Chicken Farms Enterprise / Azali Daud ... [et.al] - Daud, Azali; Jamadi, Aziz Isfarain; Jundam, Mohd Fazil; Mohamad, Mohd Khairul Azlan (Faculty of Mechanical Engineering, 2005)
With the name of Allah, the most Graceful and Merciful, for the Greatest. All the praise is to Allah and peace is upon the holy prophet Muhammad S.A.W, his family and his companions. With His permission, the business plan of ETR 300 is successfully completed. In this ETR project, we supply livestock chickens where our company's name is Maju Chicken Farm Enterprises. Maju Chicken Farm is a partnership that have four members. Our business is processing and selling chickens. This business will be operating at Pulau Indah, Selangor Darul Ehsan. Operation of our company will be starting on 13 May 2006. It is because in a year, we need to prepare the capital to build hen-houses and others equipments relative to the business. Thereafter, a signing of contract with Pertanian Pertiwi Sdn.Bhd is done as our primary supplier of raw materials. After that to complete our capital, we must submit a paper work to get loan from bank.